Motivasi dan Bentuk Kegiatan Mahasiswa dalam Menghafal Alquran; Studi Kasus Rumah Qur’an Tarqiyah - Rina Aulia Rahman; Asra Fadhilah Oktavieni; Yaser Fadillah Rilanda; Gifa Oktavia; Hany Faidza Mayori; Afifah Febriani; Silva Namira (Khalifa Journal of Islamic Education, 2018)
How glorious it is to be a memorizer of the Quran because it is placed by Allah SWT in a glorious place and can practice the Quran in daily life, but if it is not based on a strong motivation then this noble activity cannot be realized properly. This study aims to analyze the motivation of students at the Rumah Qur’an Tarqiyah in memorizing the Quran. This study uses a qualitative method with a case study approach. Sources of data were taken from five informants through in-depth interviews selected by purposive sampling technique, all informants were students who were taking part in the Quran memorization program at the Rumah Qur’an Tarqiyah. All interviews were analyzed thematically, used the Miles and Huberman technique. The research findings show seven student motivations in memorizing the Quran. The seven motivations are: i) wanting to keep the Quran, ii) getting intercession, iii) giving glory to parents, iv) wanting to be a hafiz that airs on television, v) parents’ encouragement, vi) teachers’ encouragement, vii) memorizing more the surah of the Quran. The results of this study are used as initial data for future researchers in examining this topic with different contexts and issues.